THE SIMULATION OF INFORMATION SIGNALS IN SOLVING THE TASK BEZETA-LONNIE DIAGNOSTICS OF COMPOSITE MATERIALS - Єременко, В.; Переїденко, А.; Шегедін, П. (Science-based technologies, 2011)
This paper describes the method of solving the problem of pulse signals’ synthesis during NDT of products from composite materials. The way of reducing the number of the signal’ components is reviewed. Also the algorithm of determining the distribution function coefficients of the spectral decomposition is described in the article. The results of the experiments are published.